Perception by Palpation: Development and Testing of a Haptic Ferrogranular Jamming Surface - Rørvik, Sigurd Bjarne; Auflem, Marius; Dybvik, Henrikke; Steinert, Martin (Frontiers in Robotics and AI, 2021)
Tactile hands-only training is particularly important for medical palpation. Generally, equipment for palpation training is expensive, static, or provides too few study cases to practice on. We have therefore developed a novel haptic surface concept for palpation training, using ferrogranular jamming. The concept’s design consists of a tactile field spanning 260 x 160 mm, and uses ferromagnetic granules to alter shape, position, and hardness of palpable irregularities. Granules are enclosed in a compliant vacuum-sealed chamber connected to a pneumatic system. A variety of geometric shapes (output) can be obtained by manipulating and arranging granules with permanent magnets. The tactile hardness of the palpable output can be controlled by adjusting the chamber’s vacuum level. A psychophysical experiment (N=28) investigated how people interact with the palpable surface and evaluated the proposed concept. Untrained participants characterized irregularities with different position, form, and hardness through palpation, and their performance was evaluated. A baseline (no irregularity) was compared to three irregularity conditions: two circular shapes with different hardness (Hard Lump and Soft Lump), and an Annulus shape. 100% of participants correctly identified an irregularity in the three irregularity conditions, whereas 78.6% correctly identified baseline. Overall agreement between participants was high (κ= 0.723). The Intersection over Union (IoU) for participants sketched outline over the actual shape was IoU Mdn = 79.3% for Soft Lump, IoU Mdn = 68.8% for Annulus, and IoU Mdn = 76.7% for Hard Lump. The distance from actual to drawn center was Mdn = 6.4 mm for Soft Lump, Mdn = 5.3 mm for Annulus, and Mdn = 7.4 mm for Hard Lump, being small distances compared to the size of the field. The participants subjectively evaluated the Soft Lump to be significantly softer than the Hard Lump and the Annulus. Moreover, 71% of participants thought they improved their palpation skills throughout the experiment. Together, these results show that the concept can render irregularities with different position, form, and hardness, and that users are able to locate and characterize these through palpation. Participants experienced an improvement in palpations skills throughout the experiment, which indicates the concepts feasibility as a palpation training device.